SELEKSI INDUK KAMBING BOERAWA BERDASARKAN NILAI PEMULIAAN BOBOT SAPIH DI KECAMATAN GISTING KABUPATEN TANGGAMUS - Iin Pirdania; Idalina Harris; M.Dima Iqbal Hamdani (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
Breeding Value (BV) is an evaluation of the quality of animal genetics for a certain character which isgiven relatively based on it’s position in population. This study aimed to determine the value ofweaning weight, heritability, ripitability, and BV of each individu of Boerawa goat, and to determinethe females which had the highest BV of weaning weight.The study was held in February-March 2013 in District of Gisting, Regency of Tanggamus. Themethod used in this study was survey method with 40 samples of parentstock which had record ofbreeding age at birth, pedigree of males, and goatling of female samples which had recording of birthweight, type of birth, type of maintenance, and weaning weight of the first and the second birth.Heritability was counted based on method of step brother of 1 father and ripitability was counted basedon method of corelation of interclass.Based on the study result, the averages of corrected weaning weight, value of heritability, andripitability of weaning weight, and BV of Boerawa goat in a row were 25,706±1,908 kg; 0,072±0,006(lowest category); 0,335 (medium category); 26,273±0,205 kg. Besides, there were 22 (55%) of 40Boerawa goat parentstock which had BV above the average. There were 5 parentstock with the highestBV of weaning weight, they were female goat parentstock with codes O1 (26,273), F1 (26,179), D2(25,955), H3 (25,934), and R2 (25,902).